Legislative regulation of public health in Croatia in the second half of the 19th century - Gardaš, Miro; Čandrlić, Slavko (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
PhD Student at the Doctoral Study Programme at the Faculty of Law in Osijek, Roman Law and Legal History Module Slavko Čandrlić